Macrophages Play a Key Role in the Obesity‐Induced Periodontal Innate Immune Dysfunction via Nucleotide‐Binding Oligomerization Domain‐Like Receptor Protein 3 Pathway. Issue 10 (1st October 2016) - Huang, Xin; Yu, Ting; Ma, Chanjuan; Wang, Yixiong; Xie, Baoyi; Xuan, Dongying; Zhang, Jincai
Abstract : Background: Obesity is associated with infiltration of macrophages into adipose tissue. However, effects of obesity on macrophage infiltration and activation in periodontal tissues with periodontitis are still to be elucidated. Methods: A diet‐induced obesity 16‐week mouse model was constructed, and periodontitis was induced by periodontal ligation for 10 days. The model consisted of periodontitis (P) and control (C) groups, with high fat (HF) and normal (N) diet conditions. Bone loss (BL) was analyzed by microcomputed tomography. In periodontal tissues, immunohistochemical staining and quantitative polymerase chain reaction (qPCR) detected expressions of: 1) nucleotide‐binding oligomerization domain‐like receptor protein 3 (NLRP3) pathway; 2) macrophage‐specific marker (F4/80); and 3) macrophage chemotactic protein 1 (MCP1). Bone marrow‐derived macrophages (BMDMs) from the mouse model were stimulated by Porphyromonas gingivalis lipopolysaccharide (LPS) in vitro (NC/NC + LPS: BMDMs from NC group without/with LPS stimulation; HFC/HFC + LPS: BMDMs from HFC group without/with LPS stimulation). Expressions of NLRP3 pathway in BMDMs were detected by immunocytochemical staining and qPCR. Results: BL increased significantly with periodontitis (NC versus NP; HFC versus HFP) and obesity (NP versus HFP). Expressions of NLRP3 pathway were significantly elevated in gingival tissues with periodontitis (NC versus NP; HFC versus HFP), but not with obesity (NC versus HFC; NP versus HFP). F4/80 and MCP1 expressions were significantly upregulated in gingival tissues with periodontitis (NC versus NP; HFC versus HFP) but significantly downregulated in the context of obesity (NP versus HFP). In vitro, NLRP3 pathway expressions were significantly upregulated in BMDMs after LPS stimulation (NC + LPS versus NC; HFC + LPS versus HFC), but significantly downregulated in HFC groups (HFC versus NC; HFC + LPS versus NC + LPS). Conclusion: Obesity may paralyze innate immune response of periodontium via attenuating infiltration and activation of macrophages and further aggravate periodontal disease.